Cancer cell membrane-modified biodegradable mesoporous silica nanocarriers for berberine therapy of liver cancer. Issue 70 (4th December 2018) - Yue, Juan; Wang, Zheng; Shao, Dan; Chang, Zhimin; Hu, Rui; Li, Li; Luo, Shi-zhong; Dong, Wen-fei
Abstract : We described biodegrade mesoporous silica nanoparticles coating cancer cell membrane for berberine therapy of liver cancer. Abstract : Berberine (Ber) is regarded as a new, active and natural anti-cancer product; however, its clinical application has been limited due to its low aqueous solubility, poor gastrointestinal absorption, short residence time and poor targeting abilities. Hence, we reported a biomimetic nanoparticle as a drug delivery system to surmount these obstacles. We fabricated disulfide (S–S)-bridged mesoporous organosilica nanoparticles (ss-MONs) for Ber loading, which possessed uniform morphology, controllable mesoporous properties, highly-efficient drug loading capacity and superior biocompatibility. More interestingly, ss-MONs exhibited effective biodegradability under glutathione conditions through the breakage of the disulfide bond in ss-MONs, which promoted the Ber release. After coating human liver cancer HepG2 cell membranes (CM) on the surface of ss-MONs, the obtained CM-ss-MONs-Ber enhanced accumulation in liver cancer tissue through homologous targeting and effectively avoiding rapid blood clearance. Our findings indicate that CM-ss-MONs might be desirable drug carriers to promote the clinical use of Ber against liver cancer.